Pengaruh Cita Rasa, Kualitas Pelayanan, Desain Interior, dan Digital Marketing Terhadap Kepuasan Pelanggan : Studi kasus pada kafe hachi Dusun Sidomulyo, Gitik, Kecamatan Rogojampi, Kabupaten Banyuwangi - Fitra Nahar Rizky; Suharto, Akhmad; Sari, Maheni Ika (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to determine the Influence of Taste, Service Quality, Interior Design, and Digital Marketing on Customer Satisfaction case study at cafe hachi. The method used in this study is quantitative. The data collection method was carried out by distributing questionnaires to 120 respondents who had visited cafe hachi. The data analysis method used is the multiple linear regression analysis method using SPSS Version 26 software. The results of the analysis obtained indicate that Taste, Service Quality, Interior Design, and Digital Marketing on Customer Satisfaction case study at cafe hachi, with a contribution level of influence of 0.962 or 96.2% of the results of the R2 Determination Coefficient Test. The results of this study indicate that the variables Taste, Service Quality, Interior Design and Digital Marketing partially have a positive and significant effect on Customer Satisfaction.